PROGRAM IMPLEMENTATION DELIVERY SERVICE LICENSING PADANG PARIAMAN - Muhammad Fadhil; Afriva Khaidir (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to look at the implementation of the pick-up program for the Padang Pariaman permit, which is presumed to be a problem in the implementation of the permit pick-up program. This research is a qualitative research. The technique used in determining informants in this study was carried out by purposive sampling. Informants in this study were (1) Head of the Integrated Services and Industry Services Investment Office (2) Head of the Health Office. (3) Head of the Education Office (4) Head of the Office of Environment and Spatial Planning (5). The results showed that (1) the factors that influenced the implementation of the Padang Pariaman Licensing Shuttle Program were quite successful but there were some that were still not maximal from the indicators of implementation factors (a), communication (b) Resources, (c) Disposition, (d) Bureaucratic Structure. (2) Government Efforts to improve shuttle performance in the field of licensing Efforts to Implement Public Services through the Padang Pariaman Licensing Shuttle Program (AJEP PAPA) In Kabupaten Padang Pariaman, we have always sought to maintain coordination with the relevant dinas. And when the recommendations are a problem, we always take the initiative to invite related agencies to coffee mornings and find solutions to make the program effective.